Risk Sharing in Labor Markets - Bigsten, Arne (Washington, DC: World Bank, 2014)
Empirical work in labor economics has focused on rent sharing as an explanation for the observed correlation between wages and profitability. The alternative explanation of risk sharing between workers and employers has not been tested. Using a unique panel data set for four African countries, Authors find strong evidence of risk sharing. Workers in effect offer insurance to employers: when firms are hit by temporary shocks, the effect on profits is cushioned by risk sharing with workers. Rent sharing is a symptom of an inefficient labor market. Risk sharing; by contrast, can be seen as an efficient response to missing markets. Authors evidence suggests that risk sharing accounts for a substantial part of the observed effect of shocks on wages.